Über den zentralen Grenzwertsatz von Summen der diskreten Wiederherstellungprozessen - Liutikas, V. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Лютикас. О центральной предельной теореме для сумм дискретных процессов восстановленияV. Liutikas. Apie centrinę ribinę teoremų diskretinių atstatymo procesų sumoms